Securing the Homeland: Torture, Preparedness, and the Right to Let Die - Monahan, Torin (Social justice, 2006)
Part of a special issue on immigration rights and national insecurity. The writer analyzes the discourses surrounding torture, disaster preparedness, and the right to let die in the U.S. New layers of human insecurity have been introduced through torture practices, restrictions of due process, and government spying, and resources that are badly needed for public programs are seriously depleted by the militarization of government agencies, costly wars, and privatized security forces. At the same time, moral panics are generated by and answered with disaster preparedness plans, which construct an ideal type of a responsible citizen-soldier in the ongoing battle of securing the homeland.